(3efgGL GdhUhd Edi Yde GdCUhds - (3GdHjVGhj, CHh SYjO, CHh GdNjQ, fGUQ GdOjf, YHO Gddg Hf YeQ Hf eMeO Hf Ydj(B685(3g`s ((3fUQ Gddg Hf SdeGf Hf eMeO Hf GdMGQK GdefUhQjs)
(3ChdgG (B:s
(3JbOS ef JeLO HGdYXeI hGdLdGd(B... (3hHYO aEf Chdi eG jge Gdgee GdYhGdj (B... (3hEf cJHGfG gPG efgGL GdCUhd(B...s
(3BNQgG (B:s
(3GdJGSYI(B: (3EfeG jLhR aj GaQhY hbO GNJda aj GdCUhd hdfG ajg fXQ, hdjcf gPG BNQ (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B4(3, U(B110s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B266s
(3cTa GdXfhf(B: (3L(B2(3, U(B1878s
(3GdCYdGe(B: (3L(B4(3, U(B110s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs